Isolation of A Novel Bacterial Strain Planococcus Plakortidi from Ross Broiler Chicken Gut (CECUM) with Combination of Non-Starch Polysaccride Degrading Pectinase Enzyme - Asif Raza Kanhar, Syed Fiaz Hussain, Abdul Hussain Shar,Javed Ahmed Ujjan, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: In many countries, including Pakistan, broiler chickens and the poultry industry are severely affected by bacteria. Broiler chickens are infected with Gram-positive and Gram-negative bacteria. Methods & Findings: The current study successfully isolated non-starch polysaccharide (NSP) degrading a novel strain Planococcusplakortidi (PCB2) from the chicken gut cecum, screened out from 60 samples. Practical Implication & Conclusion: Furthermore, the isolate was taxonomically characterized based on its cellular morphology, physiological, and chemotaxonomic characteristics, as well as the phylogenetic similarity index of the 16S rRNA gene sequence. The bacterium was found to exhibit maximum production of pectinase enzyme on the eighth day of incubation at 37℃. Keywords: Broiler chicken, gut microbiota, cecal bacterial diversity, chicken food digestion, Non-starch Polysaccharides